Comparison of Virulence Patterns Between Streptococcus uberis Causing Transient and Persistent Intramammary Infection - Srithanasuwan, Anyaphat; Pangprasit, Noppason; Suriyasathaporn, Witaya (Frontiers in Veterinary Science, 2022)
A study was carried out to compare virulence patterns of Streptococcus uberis as between transient and persistent intramammary infection (IMI), either from field strains or a PFGE strain with different appearance cases. For the field strains, quarter milk samples from 31 milking cows were aseptically and longitudinally collected once a week for 10 weeks. A total of 14 field S. uberis isolates from quarters with 1 and >4 weeks duration of IMI was categorized as transient and persistent S. uberis, respectively. Eleven stored isolates of a PFGE strain of S. uberis from our study (1) were randomly selected, 5 from transient IMI (1 mo) and 6 from persistent IMI (>1 mo). All isolates’ virulence profiles were investigated, including sua, hasAB, hasC, gapC, pauA, and cfu, using PCR Kaplan-Meier estimates to calculate the duration of IMI of the field strains. Approximately 50% of field S. uberis IMI was spontaneously cured within 1 week; 25% were not cured within 10 weeks. The pattern as sua+hasAB+hasC+gapC+ pauA+cfu was the major pattern in this study. The pattern without capsule formation, hasAB+hasC, was the one most found in transient strains. In addition, high similarity of the virulence gene profile within a PFGE strain was found. Evidence of 1-week spontaneous cure of most field S. uberis IMI was also found.